Analysis on Wireless Sensor Networking Applications, Classification and Challenges Mechanisms - Jayakeerthi, M (International Journal of Computer Sciences and Engineering, 2018)
Wireless sensor network is the emerging area where we are largely depending on it, in our day to day life. The major application of the wireless sensor network is the emergency navigation service during the emergency situations, and the main goal of this service is to save the people from emergency situations by guiding them to reach a safe with small congestion and fewer detours. Wireless Sensor Network will be the future of communication and it plays the vital rule of super internet in the future were all data are powered by wireless communication for transmission. This research paper discuss the techniques, key challenges and classification applications.